The Effectiveness of Gravity Fed System with Varying Media Thickness for Household Water Treatment - Pitriani Pitriani; Kiki Sanjaya; Muh. Gymnastiar (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
The availability of clean water becomes difficult during a flood disaster, one of the simple technologies that has the potential to be developed in flood-proneareas is the Gravity Fed System (GFS). The aims of the study to know the influence media thickness in GFS efektivity to reduce TSS, TDS and Total coliform. This research uses an experimental design with a laboratory test approach to see the effect of varying filter media thickness on the effectiveness of GFS. Samples were taken from the Pewana river Rogo Village in Sigi Regency. Organoleptic tests showed a significant change in color and odor parameter, from cloudy to colorless and mud smell disappears after treatment. pH (7.2-8.1) and temperature (29-32 °C) still within a quality standard. The highest effectiveness develop in sample I with a media thickness of 25 cm (TSS 96 mg/L decreased to 10 mg/L and TDS 338 mg/L to 243 mg/L), the effectiveness of 72% and 27%. GFS is effective in improving the physical quality of water where all parameters have met quality standards after treatment. The thickness of the filter media has an effect on reducing the TSS and TDS parameter, but has no effect on decreasing total coliform. Media thickness needs to be increased to improve TDS and total coliform reduction efficiency.